Comparison of the Effectiveness of Quality of Life Therapy, Positive Psychotherapy, and Compassion Therapy on Anger Management in Abused Women - Sayadifard, Roya; Atashpour, Seyyed Hamid; Yousefi, Zahra (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the effectiveness of Quality of Life Therapy, Positive Psychotherapy, and Compassion Therapy on anger management in abused women. Methodology: This research was a quasi-experimental study with a four-group design (three experimental groups and one control group) with pre-test, post-test, and follow-up phases. The statistical population included all abused women in Shahr-e Kord in 2023, from which a sample of sixty was purposefully selected and randomly assigned to four groups: Quality of Life Therapy, Positive Psychotherapy, Compassion Therapy, and a control group. While the control group was on a waiting list, the three experimental groups received eight 90-minute intervention sessions. All participants were assessed at three stages—pre-test, post-test, and follow-up—using the Anger Research Instrument (Spielberger, 1984). The collected data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (repeated measures ANOVA and Bonferroni post hoc test). Findings: The results showed that both Quality of Life Therapy and Positive Psychotherapy had a significant effect on anger management, whereas Compassion Therapy did not have a significant effect. Conclusion: Based on these results, it can be concluded that Quality of Life Therapy and Positive Psychotherapy can lead to improved anger management in women heads of households.